Constructing clarity in managerial competence : seven primitives for future research - Grenda, Dennis; Palmunen, Lauri-Matti (Springer Nature, 2025)
Research on competence has yielded a panoply of definitions of managerial competence that have caused insecurity among theorists and practitioners regarding how to deal with the competence of managers. The aim of this paper is to enhance the understanding of the construct of managerial competence. While most research on managerial competence is empirical and focuses on identifying the competencies of successful managers, we applied a conceptual approach and enhanced construct clarity by investigating the fundamental components that constitute managerial competence. In order to investigate these components, we conducted a systematic literature review and identified 31 definitions from diverse sources. Utilizing semantic decomposition, we analyzed these definitions to distill them into foundational elements. Our findings culminated in the identification of seven prime primitives: role, proficiency, disposition, capability, action, context, and effectiveness. We discuss the implications of these components in relation to construct clarity, drawing on four fundamental elements: definitions, semantic relationships to other constructs, scope conditions, and theoretical coherence. Based on our findings, we propose a research agenda consisting of four theoretical and three practical areas. A set of 7 research topics, 14 new research questions, and research methods to approach them is suggested to enable scholars and practitioners study the phenomenon in the future.